Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa dengan Menggunakan Model PRESTASI - Atsna Azizah; Herti Prastitasari (CV. ITTC INDONESIA, 2024)
This research discusses the problem of low student activity and learning outcomes due to less effective learning methods and less interesting learning. To overcome this problem, improvements were made using the PRESTASI model. This research aims to describe teacher activities, analyze increase in student activity and student learning outcomes. This research used the Classroom Action Research method with the research subjects being 23 students of class IV SDS Muhammadiyah Selat. This research uses qualitative data and quantitative data. Qualitative data was obtained by observing teacher and student activities, while quantitative data in the form of classical percentages of student activities and student learning outcomes were obtained from group and individual tests. The results of this research show that teacher activity at meeting IV met the